2020
DOI: 10.15560/16.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery and new records of Passiflora auriculata Kunth and P. cisnana Harms (Passifloraceae) in Brazil

Abstract: We present here the rediscovery of Passiflora auriculata Kunth and P. cisnana Harms in Maranhão state, northeastern Brazil, and new reports of occurrence of those species in Alagoas state, northeastern Brazil, and Tocantins state, northern Brazil. We provide taxonomic information, distribution maps, and conservation status of both species, thereby contributing to increasing knowledge on Passifloraceae in those states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…These new records expand the known distributions of P. imbeana, P. junqueirae, and P. truncata, and the recollections of P. deidamioides and P. imbeana demonstrates the importance of protected areas [including, for example, the new records of Passiflora published by Mezzonato-Pires et al (2017), Mezzonato-Pires et al (2018b), Milward-de-Azevedo (2019, Silva et al (2018), andSilva et al (2020)]. The four species are cited here for the first time in the PARNASO, occurring at elevations between 1,000 and 1,700 m.a.s.l.…”
Section: Passiflora Truncatasupporting
confidence: 55%
“…These new records expand the known distributions of P. imbeana, P. junqueirae, and P. truncata, and the recollections of P. deidamioides and P. imbeana demonstrates the importance of protected areas [including, for example, the new records of Passiflora published by Mezzonato-Pires et al (2017), Mezzonato-Pires et al (2018b), Milward-de-Azevedo (2019, Silva et al (2018), andSilva et al (2020)]. The four species are cited here for the first time in the PARNASO, occurring at elevations between 1,000 and 1,700 m.a.s.l.…”
Section: Passiflora Truncatasupporting
confidence: 55%
“…Among the eight supersections and one unplaced section included in subgenus Decaloba (see above for details), several have distinctive seed types. Cieca has fusiform to falcate (curved) seeds with coarsely reticulate‐foveate sculpture overlain by longitudinal striations (Pérez‐Cortéz et al, 2002; Vanderplank, 2004; Pérez‐Cortéz, 2007, 2016; Porter‐Utley, 2014; Hermsen, 2021; USDA, NRCS, 2022); Pterosperma has relatively large seeds (up to 12 mm long × 11 mm wide) with four striate wings (Knapp and Mallet, 1984; Gilbert and MacDougal, 2000; MacDougal and Hansen, 2003; Ulmer and MacDougal, 2004; Vanderplank, 2004; Krosnick et al, 2013a; Hermsen, 2021); and some species of supersection Auriculata , Passiflora multiflora L. in supersection Multiflora , and members of supersection Decaloba have transversely sulcate seeds (Killip, 1938; Pérez‐Cortéz et al, 2002; Ulmer and MacDougal, 2004; Vanderplank, 2004; Pérez‐Cortéz, 2007, 2016; Feuillet and MacDougal, 2008b; Krosnick et al, 2013a; Boza et al, 2018; MacDougal et al, 2018; Ocampo Pérez et al, 2018; Esquerre‐Ibañez, 2019; Silva et al, 2020; Hermsen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MacDougal & J. Ochoa (4−4.7 mm long: MacDougal et al, 2018), and P. sierrae L.K.Escobar (6 mm long: Escobar, 1989) are longer; seeds of P. auriculata , P. fanchonae , and P. rufa Feuillet & J.M. MacDougal have an apical appendage (Pérez‐Cortéz et al, 2002; Vanderplank, 2004; Pérez‐Cortéz, 2007, 2016; Silva et al, 2020); seeds of P. cryptopetala Hoehne, P. ferruginea Mast., and P. rufa have fewer ridges (five or six: Killip, 1938; Feuillet and MacDougal, 2008b), whereas seeds of P. sierrae have more ridges (13: Escobar, 1989); and the sulci on P. truncata Regel seeds are irregular (Milward‐de‐Azevedo and Baumgratz, 2004; Milward‐de‐Azevedo et al, 2012). Passiflora angusta Feuillet & J.M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Marahnão exhibits floristic potential, few studies on Bromeliaceae and other families of plants in the state are available, as shown by recently published new occurrences (e.g. Ferreira et al 2018;Guarçoni et al 2018;Ferreira et al 2019aFerreira et al , 2019bSalazar-Ferreira et al 2020;Silva et al 2020) and new species (e.g. Scatigna et al 2019;Guarçoni et al 2020).…”
Section: Introductionmentioning
confidence: 99%